Design and construction of the new library at China Agricultural University. Issue 5 (13th December 2018) - Peng, Hongtao; Zhang, Jiahui; Zhou, Zhiyuan; Mendis, Priyan; Han, Feng; Li, Zhengtao; Zhang, Du
Abstract : A new, world-class library has been built at China Agricultural University in Beijing, the oldest agricultural higher education institute in China. The new building's attractive natural stone facades reflect both old and new, from bamboo writing slips to barcodes, while the dramatic internal space is user-friendly, energy-efficient and flexible. During construction, an innovative hybrid diaphragm walling solution was adopted due to the high groundwater level and restricted site. Building information modelling technology was also successfully used throughout design and construction, helping to improve construction quality and safety management.